2011
DOI: 10.1017/s1751731111000905
|View full text |Cite
|
Sign up to set email alerts
|

Identifying risk factors for poor hind limb cleanliness in Danish loose-housed dairy cows

Abstract: The objective of this study was to identify possible risk factors for poor cow hind limb cleanliness in Danish loose-housed, lactating dairy cows. The study was conducted as a cross-sectional study of 1315 cows in 42 commercial Danish dairy herds with primarily Danish Holstein cows. The effect of four cow-level factors (parity, days in milk, daily lying time and lameness) and eight herd-level factors (herd size, milk production, milking system, floor type, access to pasture grazing, floor scraping frequency, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 25 publications
(36 reference statements)
2
20
0
Order By: Relevance
“…Similarly, a British study demonstrated that if collecting yards were scraped at least twice daily, then a small protective effect on the mastitis incidence could be determined (rate ratio = 0.90, 95% CI = 0.84-0.97, P = 0.01; Peeler et al, 2000). Although many different factors influence udder cleanliness, Danish studies also found that irrespective of udder health, lactating cows permanently housed in loose housing had an increased risk (OR = 3.75) of dirty hind limbs compared with cows permitted access to pasture, which corresponds with the results determined in the present study with respect to udder soiling (Ellis et al, 2007;Nielsen et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, a British study demonstrated that if collecting yards were scraped at least twice daily, then a small protective effect on the mastitis incidence could be determined (rate ratio = 0.90, 95% CI = 0.84-0.97, P = 0.01; Peeler et al, 2000). Although many different factors influence udder cleanliness, Danish studies also found that irrespective of udder health, lactating cows permanently housed in loose housing had an increased risk (OR = 3.75) of dirty hind limbs compared with cows permitted access to pasture, which corresponds with the results determined in the present study with respect to udder soiling (Ellis et al, 2007;Nielsen et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were found by Tucker et al (2005). Longer standing times with all four feet within the cubicles were beneficial for claw health, because claws were less exposed to manure in the alleys and could dry off more frequently (Fregonesi et al, 2009;Nielsen et al, 2011). No association of neck rail height and lameness was observed in North American dairy cattle farms (Chapinal et al, 2013).…”
Section: Effect Of Cubicle Characteristics On Animal Healthsupporting
confidence: 56%
“…Conceivably, dairy cows avoided rising in cubicles with lower neck rail heights and defecated more often while lying in the cubicle (Bernardi et al, 2009;Plesch and Knierim, 2012). Restricted neck rail positions might also lead to increased standing times in the walking alleys, which Effect of cubicle design on cattle welfare is a further risk factor for soiling (Nielsen et al, 2011;deVries et al, 2012). Contrastingly, Ruud et al (2011) did not observe an association between neck rail height and cubicle cleanliness.…”
Section: Effect Of Cubicle Characteristics On Cleanlinessmentioning
confidence: 92%
“…However, previous studies also suggested that the huge physiological, environ mental and social changes primiparous cows are faced with at first calving led to higher susceptibility to pathogens [27,30]. This can explain the larger number and proportion of affected primiparous cows in the first investigation period of the present study compared to the second investigation period.…”
Section: Paritymentioning
confidence: 52%